Produção de coagulante por uma espécie de cogumelo comestível em resíduo lignocelulósico - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
In recent decades, several researches are revealing edible mushrooms as natural sources of milk coagulant proteases, with promising characteristics for the development of dairy products. Due to the successive increase in world cheese production, there is a need for further studies to discover alternative substitutes for animal rennet. In this context, this study was carried out with the objective of evaluating the growth of Lentinus crinitus 1693 to choose nutritional sources for the production of proteases and coagulants. The species, provided by the DPUA Culture Collection, of the Federal University of Amazonas, was cultivated in PDA + Yeast Extract 0.5% (w/v). To select the culture medium to obtain the inoculum of L. crinitus, potato dextrose agar (PDA+YE), in natura potato dextrose agar (PDAIN+YE), oat agar (AA+YE), purple yam agar (Dioscorea alata) (PYA+YE), supplemented with yeast extract (YE) 0.5 % (w/v). After selection of the inoculum, the growth of L. crinitus mycelium was evaluated by solid state fermentation using cupuaçu exocarp (CC), tucumã exocarp (CT), açaí seed (SA), pineapple exocarp (CAB) and sawdust (SER), supplemented with rice bran (FA). These media were sterilized at 121 °C for two consecutive days. For cultivation on lignocellulosic substrates, three mycelial discs, measuring 8 mm in diameter, were inoculated on the surface of each waste mixture. Solid state fermentation was conducted at 25°C, in absence of light. After 15 days, coagulant proteases were extracted in sterile distilled water at 30°C, 180 rpm. The proteolytic and coagulant activities were determined using as substrate 1% azocasein solution (w/v) and 10% (w/v) skim milk, respectively, following the calculation of the coagulant ratio. The bioprocess with significant coagulant ratio was partially characterized. The results showed that PDA+YE favored the radial mycelial growth and was selected as a culture medium to obtain the inoculum of L. crinitus. Among the substrates, cupuaçu exocarp with rice bran favored the development of strongly dense mycelium, significant activity of coagulants (30.89 U) and strong clot. With optimal coagulant activity at pH 5, temperature 50 oC, stability at pH 5-7, stability at temperature 50-60 oC, presence of aspartic and serine proteases, thus favoring the possible application of these enzymes in the dairy industry.
Keywords: Cogumelos comestíveis - Cultivo; Coagulantes; Leite - Proteínas; CIENCIAS BIOLOGICAS; Amazônia; Coagulação; Fungo; Leite; Proteases